HUBUNGAN TINGKAT PEMAHAMAN KARAKTERISTIK MORFOLOGI HEWAN DENGAN KEMAMPUAN MENGHAFAL NAMA LATIN HEWAN PADA SISWA KELAS X IPA SMA NEGERI 3 JEMBER - Hasan, M Ubaidilah; Nurmawati, Ira (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
THE RELATIONSHIP OF STUDENTS' UNDERSTANDING LEVEL OF ANIMAL MORPHOLOGY CHARACTERISTICS WITH THE ABILITY TO MEMORIZE ANIMAL LATIN NAMES IN GRADE 10 IPAAbstractAnimal taxonomy subjects often use animal's Latin names. Many students think that this subject is annoying because it is dominated by memorizing animal's Latin names, even though memorizing becomes a prerequisite for understanding. Meanwhile, most of the language materials memorized need an understanding before the memorizing process. This study aimed to find a relationship between the level of students' understanding of an animal's morphological characteristics and the ability to memorize animal's Latin names at the Xth grade of IPA students in SMAN 3 Jember. This study used a quantitative approach with a type of ex post facto. The test obtained the data. Then it was descriptively and inferentially analyzed by Kendall correlation. This research indicated that 56 students who answered test of the level of understanding animal's morphological characteristics and the ability to memorize animal's Latin names resulted in a correlation coefficient of score 0.673, and significance 0,000 < 0.05. Therefore, if the level of studentsâ€™ understanding of an animal's morphological characteristics increased, the ability to memorize animal's Latin names at the Xth grade of IPA students in SMAN 3 Jember also increased, conversely. AbstrakNama latin hewan sering digunakan dalam materi taksonomi hewan. Banyak siswa beranggapan bahwa materi tersebut membosankan karena didominasi oleh menghafal nama latin hewan, padahal menghafal menjadi prasyarat pemahaman. Sementara itu, sebagian besar materi bahasa yang dihafal membutuhkan pemahaman sebelum proses menghafal berlangsung. Tujuan penelitian ini ialah mengetahui hubungan tingkat pemahaman karakteristik morfologi hewan dengan kemampuan menghafal nama latin hewan pada siswa kelas X IPA SMA Negeri 3 Jember. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis eks post facto. Data didapatkan menggunakan instrumen tes. Kemudian dianalisis secara deskriptif dan inferensial menggunakan korelasi Kendall. Penelitian ini menunjukkan bahwa dari 56 siswa yang menjawab tes tingkat pemahaman karakteristik morfologi hewan dan kemampuan menghafal nama latin hewan menghasilkan koefisien korelasi 0,673 dan signifikansi 0,000 < 0,05. Dengan demikian, jika tingkat pemahaman karakteristik morfologi hewan meningkat, kemampuan menghafal nama latin hewan pada siswa kelas X IPA SMA Negeri 3 Jember juga meningkat, begitupula sebaliknya.Â